2018
DOI: 10.1038/s41375-018-0269-8
|View full text |Cite
|
Sign up to set email alerts
|

Mlh1 deficiency increases the risk of hematopoietic malignancy after simulated space radiation exposure

Abstract: Cancer-causing genome instability is a major concern during space travel due to exposure of astronauts to potent sources of high-linear energy transfer (LET) ionizing radiation. Hematopoietic stem cells (HSCs) are particularly susceptible to genotoxic stress, and accumulation of damage can lead to HSC dysfunction and oncogenesis. Our group recently demonstrated that aging human HSCs accumulate microsatellite instability coincident with loss of MLH1 , a DNA Mismatch Repair (MMR) protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Crew members on a space mission and astronauts living on the International Space Station (ISS) can remain in space for many months at a time, where they experience a unique combination of stressors known to impact aging processes, including social isolation, confinement, microgravity, and cosmic radiation ( Giovanetti et al, 2020 ; Welsh et al, 2019 ; Kehler et al, 2019 ; Pantell et al, 2013 ; Tanskanen and Anttila, 2016 ). Although the potential negative impact of these stressors is well appreciated, the financial and physical demands of studying human aging biology in outer space have resigned some aspects of aging research to animal models or cell cultures ( Demontis et al, 2017 ; Patel et al, 2019 ). Nevertheless, research reporting mixed or unexpected relationships of space exposures with aging-related outcomes in human subjects provides continued motivation for research efforts that explicitly focus on studying humans ( Strollo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Crew members on a space mission and astronauts living on the International Space Station (ISS) can remain in space for many months at a time, where they experience a unique combination of stressors known to impact aging processes, including social isolation, confinement, microgravity, and cosmic radiation ( Giovanetti et al, 2020 ; Welsh et al, 2019 ; Kehler et al, 2019 ; Pantell et al, 2013 ; Tanskanen and Anttila, 2016 ). Although the potential negative impact of these stressors is well appreciated, the financial and physical demands of studying human aging biology in outer space have resigned some aspects of aging research to animal models or cell cultures ( Demontis et al, 2017 ; Patel et al, 2019 ). Nevertheless, research reporting mixed or unexpected relationships of space exposures with aging-related outcomes in human subjects provides continued motivation for research efforts that explicitly focus on studying humans ( Strollo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent results from Welford SM’ laboratory have demonstrated that acquired MMR deficiency and increased microsatellite instability, a commonly observed marker of DNA MMR deficiency in human hematopoietic stem and progenitor cells is age‐related, attributable to progressive loss of Mlh1 through promoter hypermethylation . The data show that as many as 30% of HSCs in healthy individuals have lost MLH1 by 45 years of age …”
Section: Discussionmentioning
confidence: 99%
“…3 However, studies on the relationship between MMR and HSC aging are not so much. [4][5][6][7] In this paper, we used RNA-Seq technology and an old hematopoietic stem and progenitor cells (HSPCs) model in vitro to analyze differential expressions of MMR-related genes in aged HSPCs, so as to explore the mechanism of DNA MMR injury in HSC aging.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these genomic studies provide compelling evidence to support a model in humans and mice without germline mutations where the formation of hematologic malignancies following exposure to ionizing radiation occurs through a non-cell-autonomous mechanism 8,46,47 . However, for individuals harboring germline mutations in DNA damage response genes, such as p53 and Mlh1 , ionizing radiation may cause blood cancers through a more direct cell-autonomous effect by increasing genomic instability in tumor-initiating cells 13,14,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, results from WES and whole-genome sequencing show distinct mutational patterns in radiation-induced cancers that develop in wild-type mice versus mice with pre-existing germline mutations. For example, using a mouse model of B-cell lymphoma, Patel et al found that gamma-rays and heavy ion ( 56 Fe) radiation markedly increased the number of insertions and deletions (indels) per tumor only in mice lacking one allele of the mismatch repair gene Mlh1 (Mlh1 +/- ) 13 . Also, using mice carrying different loss of function alleles of the tumor suppressor p53, Li et al observed that the genomic landscape of radiation-induced cancers is influenced by radiation quality, germline p53 deficiency and tissue/cell of origin 14 .…”
Section: Introductionmentioning
confidence: 99%